Clinical presentation and management challenges of sphingosine-1-phosphate lyase insufficiency syndrome associated with an SGPL1 variant: a case report - Vahid Saeedi; Nahid Rahimzadeh; Fahimeh Ehsanipour; Neda Shalbaf; Amirhosein Farahi; Khalil Rashidi; Leila Kamalzadeh (BMC Pediatrics)
Abstract Background This case report describes a unique presentation of sphingosine-1-phosphate lyase insufficiency syndrome (SPLIS) caused by a rare SGPL1 variant, highlighting the diagnostic and management challenges associated with this condition. Case presentation A 2-year-old Iranian female presented with steroid-resistant nephrotic syndrome (NS), primary adrenal insufficiency (AI), growth delay, seizures, and hyperpigmentation. Laboratory evaluation revealed hypoalbuminemia, significant proteinuria, hyperkalemia, and elevated adrenocorticotropic hormone (ACTH) levels. The patient was diagnosed with SPLIS through genetic testing, revealing a c.1018 C > T variant in SGPL1. Despite supportive treatment, including corticosteroids and cyclosporine, the patient’s condition deteriorated, leading to end-stage renal disease and sepsis, ultimately resulting in death. Conclusions This case underscores the clinical heterogeneity of SPLIS and the importance of early genetic evaluation in patients with combined NS and AI. Personalized management approaches and increased awareness among clinicians are essential to improve patient outcomes.